Alternative splicing of a single exon causes a major impact on the affinity of Caenorhabditis elegans tropomyosin isoforms for actin filaments - Ono, Shoichiro; Watabe, Eichi; Morisaki, Keita; Ono, Kanako; Kuroyanagi, Hidehito (Frontiers in Cell and Developmental Biology, 2023)
Tropomyosin is generally known as an actin-binding protein that regulates actomyosin interaction and actin filament stability. In metazoans, multiple tropomyosin isoforms are expressed, and some of them are involved in generating subpopulations of actin cytoskeleton in an isoform-specific manner. However, functions of many tropomyosin isoforms remain unknown. Here, we report identification of a novel alternative exon in the Caenorhabditis elegans tropomyosin gene and characterization of the effects of alternative splicing on the properties of tropomyosin isoforms. Previous studies have reported six tropomyosin isoforms encoded by the C. elegans lev-11 tropomyosin gene. We identified a seventh isoform, LEV-11U, that contained a novel alternative exon, exon 7c (E7c). LEV-11U is a low-molecular-weight tropomyosin isoform that differs from LEV-11T only at the exon 7-encoded region. In silico analyses indicated that the E7c-encoded peptide sequence was unfavorable for coiled-coil formation and distinct from other tropomyosin isoforms in the pattern of electrostatic surface potentials. In vitro, LEV-11U bound poorly to actin filaments, whereas LEV-11T bound to actin filaments in a saturable manner. When these isoforms were transgenically expressed in the C. elegans striated muscle, LEV-11U was present in the diffuse cytoplasm with tendency to form aggregates, whereas LEV-11T co-localized with sarcomeric actin filaments. Worms with a mutation in E7c showed reduced motility and brood size, suggesting that this exon is important for the optimal health. These results indicate that alternative splicing of a single exon can produce biochemically diverged tropomyosin isoforms and suggest that a tropomyosin isoform with poor actin affinity has a novel biological function.